SOUTH AFRICAN NATIONAL DEFENCE FORCE (SANDF) DROPS CHARGES AGAINST HIJAB-WEARING OFFICER: CASE IN POINT SOUTH AFRICA - Booley, Ashraf (Jurnal Syariah, 2021)
Over the last few decades, a piece of fabric has become a powerful and divisive symbol worldwide. Since the tragic events of 9/11, this piece of fabric has become a topic of great debate, at local, national, regional and international level. The veil as worn by some Muslim women has assumed iconic proportions around the globe. To some it symbolizes piety to others, oppression. To some it is a rejection of Western morality to others, a rejection of modernity. To some, it is a religious statement supporting Islam as a way of living; to others, a political statement supporting violent Islamists. These disparate attributions exemplify the power of nonverbal communication and support the maxim that words and objects contain no inherent meaning; only people assigned meaning. This article discusses the status of religious rights and freedoms under the South African Constitution. One aspect of this change is the change that has affected the various religions, cultures, and customs in South Africa. It is therefore, viewed by many as a constitution for the people of South Africa which includes a Bill of Rights. Historically speaking, for the very first time since colonialism, all religions were guaranteed the of religion. Furthermore, religions, cultures and languages are deep-rooted in the various constitutional provisions, namely, sections 9(3), 15(1) to (3), 30, 31, 185 and 234 respectively. These constitutional provisions are solidified by section 7 which obliges the state to respect, protect, promote and fulfil the provisions set forth in the Bill of Rights. The article concludes with an argument for the recognition of plurality of religions and religious legal systems in South Africa.